Prevalence of Cryptosporidium spp. in Yaks (Bos grunniens) in China: A Systematic Review and Meta-Analysis - Geng, Hong-Li; Ni, Hong-Bo; Li, Jing-Hao; Jiang, Jing; Wang, Wei; Wei, Xin-Yu; Zhang, Yuan; Sun, He-Ting (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptosporidium spp., the causative agent of cryptosporidiosis, can infect a variety of hosts. So far, there has been limited information regarding Cryptosporidium spp. infection in yaks (Bos grunniens). Here, we performed the first systematic review and meta-analysis for Cryptosporidium spp. infection in yaks in China. To perform the meta-analysis, five databases (Chinese National Knowledge Infrastructure (CNKI), VIP Chinese journal database, WanFang Data, PubMed, and ScienceDirect) were employed to search for studies related to the prevalence of Cryptosporidium spp. in yaks in China. The total number of samples was 8,212, and the pooled Cryptosporidium spp. prevalence in yaks was estimated to be 10.52% (1192/8012). The prevalence of Cryptosporidium spp. in yaks was 13.54% (1029/5277) and 4.49% (148/2132) in northwestern and southwestern China, respectively. In the sampling year subgroups, the prevalence before 2012 (19.79%; 650/2662) was significantly higher than that after 2012 (6.07%; 437/4476). The prevalence of Cryptosporidium spp. in cold seasons (20.55%; 188/794) was higher than that in warm seasons (4.83%; 41/1228). In the age subgroup, the yaks with age < 12 months had a higher prevalence (19.47%; 231/1761) than that in yaks with age ≥12 months (16.63%; 365/2268). Among 12 Cryptosporidium spp. species/genotypes, the C. bovis had the highest prevalence. Moreover, the effects of geography (latitude, longitude, precipitation, temperature, and altitude) and climate on Cryptosporidium spp. infection in yaks were evaluated. Through analyzing the risk factors correlated with the prevalence of Cryptosporidium spp., we recommend that effective management measures should be formulated according to the differences of different geographical factors, in order to prevent cryptosporidiosis and reduce economic losses in yaks in China.